The Impact of liquidity and Capital Adequacy and ownership percentage and debt rate of Private Insurance Companies in Syria "Case Study (Journal of Hama University, 2019)
This study addresses the problem of profitability in insurance companies and aims to analyze and discussion the impact of liquidity and capital adequacy and debt rate of National Insurance Company. Assuming that there is impact statistically significant for each of the independent variables (liquidity, capital adequacy, debt rate) in the dependent variable (ROA). By using simple regression analysis to study the relationship between each dependent variable and a dependent variable and use the multiple regression analysis to study the impact of the independent variables together in the dependent variable.  By using SPSS statistical analysis program. During the time from 2009 to 2016. The study showed inverse correlation but not statistically significant between (liquidity ratio and debt rate) and (ROA), and inverse correlation with statistically significant between (capital adequacy ratio) and (ROA). The most important results of this study are that the National Insurance Company has a high level of solvency to ensure the risk of failure to recover part of its funds and this ensures that no reduction in the capital adequacy ratio (margin of solvency) is less than 150%, which is the permissible limit. In addition, that the liquidity ratio increased during the period and this confirms that the National Insurance Company is work to take its investment decisions to not exposing to a financial difficulty.